Substrate Turnover by Transporters Curtails Synaptic Glutamate Transients - Mennerick, Steven (J Neurosci, 1999)
Although inhibitors of glutamate transport prolong synaptic currents at many glutamate synapses, the cause of the current prolongation is unclear. Transport inhibitors may prolong synaptic currents by simply interfering with synaptic glutamate binding to transporters, by inhibiting substrate translocation, or by promoting accumulation of ambient glutamate, which may act cooperatively at receptors with synaptic glutamate. We show that reversal of the membrane potential of astrocytes surrounding the synapse prolongs synaptic currents but does not decrease the apparent affinity of transporters or significantly alter glutamate-dependent kinetics of macroscopic transporter currents in excised membrane patches. Positive membrane potentials do not affect binding of a nontransported glutamate analog, nor do positive membrane potentials alter the number of transporters available to bind analog. We also test the hypothesis that glutamate accumulation during uptake inhibition by transporter substrates is the direct cause of synaptic current prolongations. Transporter substrates elevate ambient glutamate near synapses by fostering reverse transport of endogenous glutamate. However, increases in ambient glutamate cannot account for the prolongations of synaptic currents, because a nonsubstrate transport inhibitor does not foster reverse uptake yet it prolongs synaptic currents. Moreover, exogenous glutamate does not mimic synaptic current prolongations induced by substrate inhibitors. These results provide strong support for a major role of substrate translocation in determining the time course of the glutamate concentration transient at excitatory synapses.